2016
DOI: 10.1016/j.bbapap.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights from a novel invertebrate triosephosphate isomerase from Litopenaeus vannamei

Abstract: Triosephosphate isomerase (TIM; EC 5.3.1.1) is a key enzyme involved in glycolysis and gluconeogenesis. Glycolysis is one of the most regulated metabolic pathways, however little is known about the structural mechanisms for its regulation in non-model organisms, like crustaceans. To understand the structure and function of this enzyme in invertebrates, we obtained the crystal structure of triosephosphate isomerase from the marine Pacific whiteleg shrimp (Litopenaeus vannamei, LvTIM) in complex with its inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…The topology of this tree also suggests that TPIs from green algae, like C. reinhardtii , have followed a distinct evolutionary trajectory in comparison to plastidic TPI form land plants (Figure 2B ). A superimposition of the crystal structure of SyTPI with TPIs crystalized in the absence of ligand (AtcTPI and AtpdTPI) (Figure 2C ) illustrates that SyTPI exhibits a closed loop 6 conformation (Mande et al, 1994 ; Lopez-Zavala et al, 2016 ). This superposition also indicates that the secondary structural elements of SyTPI are virtually identical between photosynthetic TPIs.…”
Section: Resultsmentioning
confidence: 99%
“…The topology of this tree also suggests that TPIs from green algae, like C. reinhardtii , have followed a distinct evolutionary trajectory in comparison to plastidic TPI form land plants (Figure 2B ). A superimposition of the crystal structure of SyTPI with TPIs crystalized in the absence of ligand (AtcTPI and AtpdTPI) (Figure 2C ) illustrates that SyTPI exhibits a closed loop 6 conformation (Mande et al, 1994 ; Lopez-Zavala et al, 2016 ). This superposition also indicates that the secondary structural elements of SyTPI are virtually identical between photosynthetic TPIs.…”
Section: Resultsmentioning
confidence: 99%
“…through unfolding experiments concluded that this residue 45 in TvTIMs controls the dimer‐monomer equilibrium . In whiteleg shrimp ( Litopenaeus vannamei ) residue 47 ( 45 ) is a C, involved in intersubunit contact, the mutation C47A ( 45 ) has a very similar catalytic efficiency but is less stable in experiments of thermal denaturation . See also 17 . Residue 47 ( 46 ) is a H in TbTIM.…”
Section: Effect Of Specific Residues At Selected Positionsmentioning
confidence: 99%
“…A single dataset was integrated and scaled using XDS and XSCALE respectively [30]. Phases were solved by molecular replacement using the program PHASER [31] and the crystal structure of TPI from Litopenaeus vannamei [49] as a search model. Initial model and refinement were executed using COOT and PHENIX.…”
Section: Protein Crystallography and Structural Determinationmentioning
confidence: 99%